Boron toxicity affects plant growth by destroying the cell membrane stability and micronutrient balance in melon - Gamze Kaya (Scientific Reports)
Abstract This study focused on the toxic effects of boron (B) on the growth and micronutrient composition of melon plants. The seedlings were grown in pots with different concentrations of B (0, 20, 40, 60, and 80 mg B/kg soil) for 30 days. Plant height, seedling fresh and dry weight, leaf number, area, temperature, dry matter, chlorophyll index (Chl), relative water content (RWC), and cell membrane stability (CMS) were measured. B, Fe, Mn, Zn, and Cu in the shoots and soil B were determined. Increasing B linearly decreased plant height, while 20 mg B/kg stimulated fresh weight, leaf number, and area. However, seedling growth was inhibited at concentrations higher than 40 mg B/kg. The RWC and Chl were not changed between the control and 60 mg B/kg. Conversely, applying 20 or 40 mg B/kg improved the CMS. Increasing B caused a linear increase in B in plant tissues while disturbing the ionic balance with Fe, Mn, Zn, and Cu. It was concluded that increasing B caused a detrimental reduction in Chl, RWC, CMS, and Fe concentration, whereas the leaf temperature increased, resulting in the inhibition of root, stem, and leaf growth in melon plants.